Effect of Temperature and Chloride Concentration on the Anodic Formation of Nanoporous Gold Films in Chloride Solutions. (24th August 2015) - Kim, Minju; Jeong, Hwakyeung; Lee, Euna; Kim, Jongwon
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10463-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>